Zircon U–Pb isotopes and trace element data from samples in the Majorqaq Belt, Greenland (IEDA: EarthChem Library)
This dataset contains LA-ICP-MS results of U-Pb and trace element data from metasedimentary rocks that were sampled from the Majorqaq Belt, southern West Greenland.